Chromosome 1 amplification has similar prognostic value to del(17p13) and t(4;14)(p16;q32) in multiple myeloma patients: analysis of real-life data from the Polish Myeloma Study Group - Grzasko, Norbert; Hajek, Roman; Hus, Marek; Chocholska, Sylwia; Morawska, Marta; Giannopoulos, Krzysztof; Czarnocki, Krzysztof; Druzd-Sitek, Agnieszka; Pienkowska-Grela, Barbara; Rygier, Jolanta; Usnarska-Zubkiewicz, Lidia; Dytfeld, Dominik; et al. (Leukemia & lymphoma, 2017)
The study aimed to assess prognostic significance of del(13q14), del(17p13), t(4;14)(p16;q32), and amp(1q21) in newly diagnosed myeloma patients treated mostly with thalidomide-based therapies. All genetic abnormalities except del(13q14) were independent prognostic factors associated with shortened progression-free survival (PFS) and overall survival (OS). Patients with no abnormalities, one abnormality, and ≥2 abnormalities had a median PFS of 41.8, 17.0, and 10.0 months, respectively; a median OS was not reached, 48.0 and 23.3 months, respectively. According to the presence of amp(1q21), t(4;14)(p16;q32), and del(17p13) and the International Staging System (ISS), we stratified patients into low-risk, intermediate-risk and high-risk groups. A median PFS was 52.9, 25.6, and 10.0 months, respectively; a median OS was not reached, 64.0 and 25.0 months, respectively. In conclusion, our study confirmed the prognostic value of cytogenetic changes and showed that prognostic models based on ISS and cytogenetic studies should include not only del(17p13) and t(4;14)(p16;q32), but also amp(1q21).
Keywords: senioři; lidské chromozomy, pár 17; analýza přežití; Poland; senioři nad 80 let; Multiple Myeloma; prognosis; hybridizace in situ fluorescenční; Retrospective Studies; Survival Analysis; Incidence; Prognosis; Chromosomes, Human, Pair 17; lidské chromozomy, pár 4; mužské pohlaví; duplikace chromozomů; incidence; Multiple myeloma; Polsko; In Situ Hybridization, Fluorescence; thalidomide; lidské chromozomy, pár 1; Aged, 80 and over; mnohočetný myelom; ženské pohlaví; prognóza; chromozomální delece; retrospektivní studie; Chromosomes, Human, Pair 14; Humans; cytogenetic abnormalities; Chromosome Deletion; Translocation, Genetic; Chromosomes, Human, Pair 1; Chromosomes, Human, Pair 4; translokace genetická; Female; Aged; Chromosome Duplication; lidé; Male; lidské chromozomy, pár 14